Noting the external dimensions of the Bisaldeo Temple - Temples of India Project Team (Jio Institute, 2024)
Ar. Urvi Manani noting the external dimensions of the structure of Bisaldeo Temple, Tonk district, Rajasthan. (Image courtesy: Mrunal Nidadavolu)